Peran Citicoline Oral Sebagai Terapi Tambahan dalam Pengobatan Glaukoma - Sinaga, Wina (PT Kalbe Farma Tbk., 2024)
Glaucoma is the second-leading global cause of blindness. Lowering intraocular pressure can prevent the worsening of open-angle glaucoma, but alternative neuroprotective therapies are needed; citicoline is supposed to have neuroprotective potential. This evidence-based case report was to review the effectiveness of oral citicoline as an adjunct therapy for glaucoma. From 22 studies identified through PubMed, Scopus, Cochrane, EBSCO Host, and Google Scholar, three articles were selected for critical review. Lanza M. found the RNFL and GCC of the citicoline group 500 mg were significantly higher, 70.39 and 71.19 Pm, p<0,01 compared to controls, after 12 months. Sahin A, et al, showed that the RNFL was significantly higher in the third month than baseline in the oral citicoline 250 mg group, p = 0.038. Putri VC, et al, found that after 60 days, based on sub-group analysis, there was a significant difference in RNFL and GCIPL thickness changes after citicoline 500 mg intervention in the mild glaucoma group and after citicoline 1,000 mg in the moderate-severe glaucoma group. Oral citicoline supplementation prevents significant worsening of glaucoma, it can be given as an adjunct therapy.